2016
DOI: 10.1177/1550059416644887
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution Electromagnetic Fields Exposure Modulates the Resting State EEG on Alpha and Beta Bands

Abstract: Long-term evolution (LTE) wireless telecommunication systems are widely used globally, which has raised a concern that exposure to electromagnetic fields (EMF) emitted from LTE devices can change human neural function. To date, few studies have been conducted on the effect of exposure to LTE EMF. Here, we evaluated the changes in electroencephalogram (EEG) due to LTE EMF exposure. An LTE EMF exposure system with a stable power emission, which was equivalent to the maximum emission from an LTE mobile phone, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Very few studies have examined EDA under mobile phone (MP) exposure; however, several studies on the effect of EMF on EEG have shown a consistent effect of MP on the EEG by increasing or decreasing alpha (8-13 Hz) power (Reiser et al, 1995;Croft et al, 2002;Huber et al, 2002;Karamenko et al, 2003;Cook et al, 2004;Curcio et al, 2005;Maby et al, 2006;Perentos et al, 2007;Regel et al, 2007;Vecchio et al, 2007;Hinrikus et al, 2008;Vecchio et al, 2012;Perentos et al, 2013;Ghosn et al, 2015;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have examined EDA under mobile phone (MP) exposure; however, several studies on the effect of EMF on EEG have shown a consistent effect of MP on the EEG by increasing or decreasing alpha (8-13 Hz) power (Reiser et al, 1995;Croft et al, 2002;Huber et al, 2002;Karamenko et al, 2003;Cook et al, 2004;Curcio et al, 2005;Maby et al, 2006;Perentos et al, 2007;Regel et al, 2007;Vecchio et al, 2007;Hinrikus et al, 2008;Vecchio et al, 2012;Perentos et al, 2013;Ghosn et al, 2015;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that one study assessed not only the effect of phone use, but also the mixed effect of caffeine and simultaneous MP exposure. Typically, double/single blind randomized counterbalanced crossover design was used [Lowden et al, ; Volkow et al, ; Curcio et al, ; Schmid et al, ,; Vecchio et al, ; Loughran et al, ; Lv et al, ; Ghosn et al, ; Roggeveen et al, ; Yang et al, ], in which participants were exposed to two different conditions. In the sham condition, the MP was switched “on” but without global system for mobile communication (GSM) RF; in the real condition, the phone was switched “on” with GSM RF.…”
Section: Resultsmentioning
confidence: 99%
“…The inconsistency could partly be attributed to different exposure frequencies, modulation modes, and exposure durations [Zhang et al, ]. For 4G‐related signals, only our two previous studies have investigated the acute effect of long‐term evolution (LTE) EMF exposure on human brain function [Lv et al, ; Yang et al, ] using EEG and functional magnetic resonance imaging (fMRI). We found that 30 min of LTE‐EMF exposure modulated the alpha/beta EEG bands [Yang et al, ] and spontaneous low‐frequency fluctuations [Lv et al, ] in some brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…For 4G‐related signals, only our two previous studies have investigated the acute effect of long‐term evolution (LTE) EMF exposure on human brain function [Lv et al, ; Yang et al, ] using EEG and functional magnetic resonance imaging (fMRI). We found that 30 min of LTE‐EMF exposure modulated the alpha/beta EEG bands [Yang et al, ] and spontaneous low‐frequency fluctuations [Lv et al, ] in some brain regions. Since LTE networks have been widely deployed, we should make more effort to evaluate the possible effects of LTE‐EMF exposure from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation